Aspekte gemeinsamer Agrarpolitik 2002; Agricultural Policy 2002 - Dirk Manegold (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– The agricultural policy discussion in Germany was dominated last year by the European Commission's Mid-term Review of the Agenda 2000 and by the process of EU enlargement. Proceedings at WTO issues were less visible to the public but the Doha round of multilateral trade negotiations remained present in all discussions at least as a key argument in favour of continued agricultural policy reform. The Mid-term Review proposed some further reductions in price support and unexpectedly called for a deeprooted change in direct payments. Besides advocating a complete decoupling of payments it suggested a progressive decrease in the level of direct payments in order to save monetary resources for funding measures of more general rural development. With regard to EU enlargement, negotiations have finally been completed due to further compromises especially in the fields of financial transfers and agricultural quotas. Entry of ten new member countries is now scheduled to take place on May 1st, 2004.
Keywords: 330; EU-Agrarpolitik; EU-Mitgliedschaft; Agraraußenhandel; EU-Staaten; Deutschland